Endocytoscopy for the diagnosis of marginal zone B‐cell lymphoma of mucosa‐associated lymphoid tissue type in the rectum: Report of two cases. Issue 4 (28th November 2019) - Satoh, Tatsunori; Hotta, Kinichi; Imai, Kenichiro
Abstract : Watch a video of this article